ADSORPSI ION TEMBAGA(II) MENGGUNAKAN AMPAS DAUN TEH SEBAGAI ADSORBEN - Rizki, Diah (CHEMISTRY PROGRESS, 2010)
ABSTRACT Gusti, D. R. and A. Wuntu, 2010. Absorption of Cupper (II) ion using tea leaves dregs as adsorbent.An investigation on the adsorption of copper (II) by using the dregs of tea leaves as an adsorbent. The research results are obtained that the adsorption of metal ions Cu (II) with a concentration of 500 mg /L at the dregs of tea leaves as adsorbent 0.1 g for 20 minutes has a contact time of equilibrium at 190-200 minutes. This adsorption followed the Freundlich isotherm model. Adsorption process is highly dependent on initial concentration, the higher the initial concentration of metal ions Cu (II), the higher the concentration of metal ions Cu (II) adsorbed. Adsorption capacity of Cu (II) on waste tea leaves are estimated from graphs isoterm adsorption worth more than 45 mg for every gram of adsorbent.Keywords : adsorption, ion copper (II), waste tea leaves, and adsorption capacity